2017
DOI: 10.1038/onc.2016.465
|View full text |Cite
|
Sign up to set email alerts
|

A targetable HB-EGF–CITED4 axis controls oncogenesis in lung cancer

Abstract: Aberrant epidermal growth factor (EGF) receptor (EGFR) signaling contributes to neoplastic initiation and progression in lung. Mutated EGFR has become as an important therapeutic target in lung cancer, whereas targeted treatment is not available for wild-type EGFR or its ligands. In this study, we found that heparin-binding (HB)-EGF, a member of the EGF family, was highly expressed in a subset of lung cancer, proliferation of which was dependent on HB-EGF signaling. Silencing of HB-EGF with RNA interference in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 39 publications
0
16
1
Order By: Relevance
“…Our data showed arsenic exposure caused HB-EGF to stimulate EGFR phosphorylation (p-EGFR) at Tyr 1068 and confirmed HB-EGF was highly expressed in As-T cells and most tumor tissues samples of 35 lung cancer cases. The latter observation consist with study by Yotsumoto and Hsieh that HB-EGF is the predominant EGFR ligand in lung cancer cells and EGFR mutation and that HB-EGF expression predicts poor survival in patients with primary lung tumors ( 35 , 36 ).…”
Section: Discussionmentioning
confidence: 89%
“…Our data showed arsenic exposure caused HB-EGF to stimulate EGFR phosphorylation (p-EGFR) at Tyr 1068 and confirmed HB-EGF was highly expressed in As-T cells and most tumor tissues samples of 35 lung cancer cases. The latter observation consist with study by Yotsumoto and Hsieh that HB-EGF is the predominant EGFR ligand in lung cancer cells and EGFR mutation and that HB-EGF expression predicts poor survival in patients with primary lung tumors ( 35 , 36 ).…”
Section: Discussionmentioning
confidence: 89%
“…Heparin-binding epidermal growth factor (HB-EGF) is an epidermal growth factor receptor (EGFR) cognate ligand with mitogenic and chemotactic properties for fibroblasts and smooth muscle cells [262]. H. pylori infection results in the upregulation of HB-EGF gene expression, which is a potential serological biomarker for gastric cancer [263][264][265][266][267].…”
Section: Heparin-binding Epidermal Growth Factor and Matrix Metalloprmentioning
confidence: 99%
“…In wound healing assays, cellular damage by the scratch releases ATP, which stimulates the shedding of HB-EGF mediating the transactivation of EGFR ( Yin et al, 2007 ) could drive the differential migration of FBLN1 knockdown cells. Studies have shown FBLN1C binds HB-EGF ( Brooke et al, 2002 ), which is a prominently overexpressed ligand for EGFR in NSCLC ( Hsieh et al, 2017 ; Yotsumoto et al, 2017 ). This could in part contribute to the differential effect FBLN1C has relative to FBLN1D in EGFR dependent migration and wound closure.…”
Section: Discussionmentioning
confidence: 99%